Средства огневой зачистки металла - Дайкер А. Л. Артур Львович; Шулаев И. П. Иван Петрович; Вейс А. И. Анатолий Иванович; Богатырев А. Д. Анатолий Дмитриевич; Рыбин В. С. Владимир Семенович (Москва, Металлургия, 1987)
Авт. указаны на обороте тит. л.